Pengaruh Penggunaan Ice Breaking terhadap Konsentrasi Belajar Pendidikan Agama Kristen dan Budi Pekerti Siswa Kelas XI SMK Negeri 2 Balige Tahun Pembelajaran 2023/2024 - Sri Devi Sinaga; Senida Harefa; Limmarten Simatupang (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
The purpose of this study was to determine the effect of the use of Ice Breaking on the concentration of learning Christian Religious Education and Budi Pekerti class XI students of SMK Negeri 2 Balige Learning Year 2023/2024. The research hypothesis is: “there is a positive and significant effect of the use of Ice Breaking on the concentration of learning Christian Religious Education and Ethics of Grade XI Students of SMK Negeri 2 Balige in the 2023/2024 Learning Year”. The population is all XI grade students majoring in BDP at SMK Negeri 2 Balige, Toba Regency, Learning Year 2023/2024, totaling 126 people. The research sample was determined using purposive sampling technique, namely students in class XI BDP 1 totaling 32 people as a control class using conventional methods and class XI BDP 3 totaling 32 people as an experimental class using Ice Breaking. This research method is a quantitative approach with a true experimental design method and with a post-test only control group design. The instrument used in this research is a questionnaire item for variable Y as many as 30 items. Research data for questionnaires were analyzed using the Separated Variance t test formula. From the calculation results obtained the value of tcount = 4.337 > ttable (α = 5%) = 1.671. The tcount value is in the H0 rejection curve area and Ha acceptance. Thus it can be concluded that the research hypothesis is accepted, namely that there are differences in the concentration of learning Christian Religious Education and Budi Pekerti class XI students of SMK Negeri 2 Balige Learning Year 2023/2024 who are taught before and after ice breaking.